MOTIVASI PASANGAN USIA SUBUR (PUS) MENGGUNAKAN METODE KONTRASEPSI JANGKA PANJANG (MKJP) DI KECAMATAN MARTAPURA KABUPATEN BANJAR PROVINSI KALIMANTAN SELATAN - Siti Zakaria Lestari; Deasy Arisanty; Ellyn Normelani (Universitas Lambung Mangkurat, 2018)
This research entitled, “entitled Motivation spouses of fertile age ( PUS ) Using Long Term Contraception Method ( LTCM ) in the district of South Kalimantan MartapuraBanjar district” . This study aimed to use the EFA motivation Long -term contraception method ( LTM ) in District MartapuraBanjar district . The population in this study are spouses of fertile age ( PUS ) Participants KB active totaling 2,149 inhabitants in the district Martapura using the technique of taking random ie all spouses of fertile age ( PUS ) District of Martapura the planning participants active equal opportunities to be selected into the sample with a view on the tables Isaac and Michale obtained MartapuraSubdistrict samples totaling 327 respondents. The method used diskriftif with quantitative approach . Data collection techniques are primary data obtained from questionnaires , while secondary data obtained from the study of documents and studies pustak . Sampling was conducted using sampling techniques probality . Data analysis technique used is the percentage and scoring techniques . The description and analysis of the data described can be interpreted as motivational couples of childbearing age use a long-term contraceptive methods in District MartapuraBanjar district can be said to be high . The results showed motivation is an impulse that drives a person to behave , distribute and berintraksi to the situation. Motivation spouses of fertile age ( PUS ) MartapuraSubdistrict Using Long Term Contraception Method ( LTM ) . Intrinsic motivation and extrinsic motivation that affects spouses of fertile age ( PUS ) Using Long Term Contraception Method ( LTM ) m ie Age / age , level of knowledge , level of education . Extrinsic motivation that affects spouses of fertile age ( PUS ) Using Long Term Contraception Method ( LTM ) is the level of employment .